Guinness world records 2002 - Cunningham, Antonia ([N.Y.] : Bantam Books., 2001)
Completely revised and updated for 2002, this book presents thousands of world records on sports, weather, buildings, businesses, disasters, and more.
Keywords: Curiosities and wonders -- Miscellanea. -- Knowldege and facts -- Miscellanea